ANALISIS FAKTOR-FAKTOR DOMINAN YANG MEMPENGARUHI KEMISKINAN DI PROVINSI RIAU - Widya Ningsih Zebua; Djaimi Bakce; Syaiful Hadi (Indonesian Journal of Agricultural Economics, 2015)
There are many factors respect to poverty, but to recommand the exactly policy for reducting poverty need to identified the dominant factors. This study aims to analyze the dominant factors that respect to poverty in Riau Province. The data used in this study is time series data about poverty in 1993-2012. Therefore, the model used in this sudy is multiple regression equation model with Ordinary Least Square method. The result show that the dominant factors that respect to poverty in Riau Province are time of school, life expectation, and unemployment. Recommendation of this study to reducting poverty by increasing time of school, life expectation and reducting unemployment. To increase time of school could be done by implementation of 12 years education program by providing scholarships for poor households. The life expectation could be increase by giving free health service to poor households. Furthermore, to reducting unemployment it also needs implementing the intensive development programs by involve poor housholds.